Oil Refining: Cross-Elasticities of Supply 1 - Manne, Alan S. (Quarterly Journal of Economics, 1951)
I. Introduction, 214. — II. Time series comparisons, 222. — III. Regional comparisons, 228. — IV. Cracking and recycling data, 230. — V. Conclusions, 235.